Phosphoinositide-Dependent Protein Kinases Regulate Cell Cycle Progression Through the SAD Kinase Cdr2 in Fission Yeast - Liu, Kun; Liu, Qiannan; Sun, Yanli; Fan, Jinwei; Zhang, Yu; Sakamoto, Norihiro; Kuno, Takayoshi; Fang, Yue (Frontiers in Microbiology, 2022)
Aberration in the control of cell cycle contributes to the development and progression of many diseases including cancers. Ksg1 is a Schizosaccharomyces pombe fission yeast homolog of mammalian phosphoinositide-dependent protein kinase 1 (PDK1) which is regarded as a signaling hub for human tumorigenesis. A previous study reported that Ksg1 plays an important role in cell cycle progression, however, the underlying mechanism remains elusive. Our genomic library screen for novel elements involved in Ksg1 function identified two serine/threonine kinases, namely SAD family kinase Cdr2 and another PDK1 homolog Ppk21, as multicopy suppressors of the thermosensitive phenotype of ksg1-208 mutant. We found that overexpression of Ppk21 or Cdr2 recovered the defective cell cycle transition of ksg1-208 mutant. In addition, ksg1-208 Δppk21 cells showed more marked defects in cell cycle transition than each single mutant. Moreover, overexpression of Ppk21 failed to recover the thermosensitive phenotype of the ksg1-208 mutant when Cdr2 was lacking. Notably, the ksg1-208 mutation resulted in abnormal subcellular localization and decreased abundance of Cdr2, and Ppk21 deletion exacerbated the decreased abundance of Cdr2 in the ksg1-208 mutant. Intriguingly, expression of a mitotic inducer Cdc25 was significantly decreased in ksg1-208, Δppk21, or Δcdr2 cells, and overexpression of Ppk21 or Cdr2 partially recovered the decreased protein level of Cdc25 in the ksg1-208 mutant. Altogether, our findings indicated that Cdr2 is a novel downstream effector of PDK1 homologs Ksg1 and Ppk21, both of which cooperatively participate in regulating cell cycle progression, and Cdc25 is involved in this process in fission yeast.